Financial inclusion of rural smallholder farmers in Nigeria : measurement issues, impact on livelihood and implications for policy interventions - Machethe, Charles Lepepeule (University of Pretoria, 2021)
Thesis (PhD (Agricultural Economics))--University of Pretoria, 2021.